Insulin-like growth factor-II (IGF2) gene of zebrafish and its use as a biogenetic marker for the assay of epigenetic toxin exposure - Alazzabi, Mufida (University of Ottawa (Canada), 2004)
The purpose of this research was to determine whether expression analysis of the IGF2 gene in zebrafish, a gene whose transcription is known to be regulated by DNA methylation in mammals, can be used as a marker or indicator of DNA methylation due to toxin exposure in fish embryos. We examined the expression of IGF2, IGF1, and IGFBP-1 in zebrafish embryos treated with sodium arsenite (thought to inhibit DNA methylation), nickel chloride (thought to cause DNA hypermethylation), trichostatin A (a histone deacetylase inhibitor), 5-azaC (thought to cause methyltransferase inhibition), cadmium chloride (thought to cause DNA hypermethylation) and mercury chloride (unknown). (Abstract shortened by UMI.)
Keywords: Biology, Molecular.